IMPLANTED RADIOGENIC AND OTHER NOBLE GASES IN CRUSTAL DIAMONDS FROM NORTHERN KAZAKHSTAN - Verchovsky A.B.; Ott U.; Begemann F. (My University, 1993)
Noble gases were extracted in steps from grain size fractions of microdiamonds (less than 100 microns) from the Kokchetav Massif, Northern Kazakhstan, by pyrolysis and combustion. The concentration of He-4 in the diamonds proper (liberated by combustion) shows a 1/r dependence on grain size. For grain diameters greater than 15 microns the concentration also decreases with the combustion step. Both results are clear evidence that He-4 has been implanted into the diamonds from alpha-decaying elements in the surrounding matrix. The saturation concentration of He-4. (5.6 x 10(exp -4) cu cm STP/g) is among the very highest observed in any terrestrial diamonds. Fission xenon from the spontaneous fission of U-238 accompanies the radiogenic He-4; the (136)Xe(sub f)/He-4 ratio of (2.5 +/- 0.3) x 10(exp -9) agrees well with the production ratio of 2.3 x 10(exp -9) expected in a reservoir where Th/U about 3.3. Radiogenic Ar-40 is predominantly (greater than 90%) set free upon combustion; it also resides in the diamonds and appears to have been incorporated into the diamonds upon their formation. He-3, on the other hand is mainly released during pyrolysis and hence is apparently carried by 'contaminants'. The concentration in the diamonds proper is of the order of 4 x 10(exp -12) cu cm STP/g, with a He-3/He-4 ratio of 1 x 10(exp -8). Excess Ne-21, similarly, appears to be present in contaminants as well as in diamonds proper. These two nuclides in the contaminants must have a nucleogenic origin, but it is difficult to explain their high concentrations.